Residue Retention and Potassium Nitrate Improvise the Yield and Economics of Wheat Crop - Jaidka, Manpreet; Singh Brar, Amandeep (International Journal of Economic Plants, 2024)
The experiment was conducted during rabi (October, 2021-April, 2022) season at farmers’ field in the NICRA adopted village Meenia, District Moga, Punjab to check the integrated effect of crop residue management practices and KNO3 spray on the productivity of wheat crop. The trial was replicated four times with eight treatments viz., conventional sowing by residue burning, conventional sowing by residue burning fb foliar spray of KNO3 (2%) at heading and anthesis stage, sowing of wheat with happy seeder, sowing of wheat with happy seeder fb foliar spray of KNO3 (2%) at heading and anthesis stage, sowing of wheat with surface seeding, sowing of wheat with surface seeding fb foliar spray of KNO3 (2%) at heading and anthesis stage, sowing of wheat after incorporation of paddy straw, sowing of wheat after incorporation of paddy straw fb foliar spray of KNO3 (2%) at heading and anthesis stage. Results showed that surface seeding fb KNO3 spray, happy seeder technology fb KNO3 spray recorded significantly higher 1000 grain weight than conventional tillage. Surface seeding and KNO3 spray recorded highest grain yield (4.91 t ha-1) followed by happy seeder and KNO3 spray (4.84 t ha-1). A synergistic effect between CRM technologies and foliar application of KNO3 was recorded where they resulted in 16.65 (4.84 t ha-1), 18.34 (4.91 t ha-1) and 5.38% higher grain yield in comparison to conventional sowing (4.15 t ha-1). A highly significant positive correlation (r=0.449) was recorded between number of grains ear-1 and grain yield. Surface seeding and happy seeder technology significantly increased net returns and B:C of wheat crop than conventional practices.